MATRICONDITIONING PLUS BERBASIS TRICHODERMA HARZIANUM DAN BERBAGAI JENIS MATRIKS UNTUK REVITALISASI BENIH KEDELAI (Glycine max L. Merr.) KEDALUWARSA - Putri Santika; Fammi Sella Arinda Putri; Ilham Muhklisin; Dewi Fatmawaty Sabiku (Journal of Innovation Research and Knowledge, 2026)
Soybean (Glycine max L. Merr.) seeds are susceptible to deterioration during storage, resulting in reduced viability and vigor. Matriconditioning plus, which combines controlled hydration with beneficial microorganisms, offers a promising approach to improve seed quality. This study evaluated the effects of different matrix materials and Trichoderma harzianum on the physiological quality of expired soybean seeds. A completely randomized factorial design was used with two factors: matrix type (rice husk charcoal, sawdust, and vermiculite) and T. harzianum application (without and with T. harzianum). Seed quality was evaluated based on germination percentage, mean germination time (MGT), vigor index, germination rate, and germination uniformity. The combination of sawdust and T. harzianum produced the highest germination percentage (68.75%), vigor index (44.75%), germination rate (18.26% etmal⁻¹), and germination uniformity (40.75%). Sawdust was the most effective matrix material, while T. harzianum significantly improved germination percentage, vigor index, germination rate, and germination uniformity but did not affect MGT. These findings indicate that matriconditioning plus using sawdust and T. harzianum is an effective seed invigoration technique for improving the viability and vigor of expired soybean seeds.